Overview of the world's medical schools: an update. Issue 9 (September 2014) - Duvivier, Robbert J; Boulet, John R; Opalek, Amy; van Zanten, Marta; Norcini, John
<x xml:space="preserve">Abstract</x> Discuss ideas arising from the article at 'discuss'